Enhancing nutrients availability using enriched biochar produced from selected wastes to promote Oryza sativa (MR297) growth in acidic soil - Gunavathy Selvarajh (2022)
The rice residues and chicken manure were abundant. Usually, the wastes were burnt or dumped in streams which cause environmental problems. Simultaneously, around 60% - 80% of nitrogen were lost in the form of ammonia to the environment from the applied urea fertilizer in irrigated lowland rice field. This causes nitrogen deficiency in soil and reduces the rice yield by 40 kg ha-1 - 55.8 kg ha-1. A solution to address the wastes abundancy problem and nitrogen loss in rice field is to convert the rice wastes into biochar, and further enrich it with chicken manure to increase the nutrient content, surface area, and porosity of the biochars. The enriched biochars produced will be able to adsorb ammonia from the applied urea fertilizer in the rice field, and this paves a better way to reduce agricultural waste, ammonia volatilization, fertilizer importing cost, and increase rice yield. The objectives of the study were to; (1) convert rice straw and rice husk into biochars through charring process and enriched with chicken manure followed by characterization. (2) determine the effect of amending urea with enriched rice straw and rice husk biochars on ammonia loss from urea, soil total nitrogen, exchangeable ammonium, and available nitrate, (3) determine whether urea amended with enriched biochars could improve the nutrients uptake, biomass production, nutrient use efficiency, and yield of rice cultivation on a tropical acid soil, and (4) estimate the cost-benefit between the chemical fertilization and enriched biochars application in the cultivation of MR297. The effectiveness of enriched biochars were assessed in laboratory incubation study, pot study, and field trials. The incubation study revealed that the application of 5 - 10 t ha-1 of the enriched biochars had delayed the ammonia loss by 5 - 7 days. The application of enriched biochars at rate of 5 - 10 t ha-1 had significantly increased the soil total carbon, cation exchange capacity, total nitrogen, exchangeable ammonium, and available nitrate in pot experiment over control in pot experiment. The enriched biochars also had significantly increased soil pH, and reduced soil exchangeable acidity, aluminium, and iron compared to control. The rice plant physical growth, dry matter production, and nitrogen uptake in treatments amended with enriched biochars had shown a significant positive increment over control. The rice grain yield in treatments amended with enriched biochars was increased by 30% - 38% in field cycle I and 38% - 49.7% in field cycle II compared to control. The economic analysis had exerted that the net profit obtained in treatments amended with 5 t ha-1 rice husk biochar was the highest in both field cycles, namely, RM 8,864.59 and RM 11,016.60, respectively. Thus, 5 t ha-1 rice husk biochar application can be adopted to delay and minimize ammonia loss from urea fertilizer, while increasing the adsorption of the soil exchangeable ammonium, which can improve plant nitrogen uptake for better yielding. Further study on the residual effect of the enriched biochar on soil nutrients and plant growth is needed to allow long term observation in the economic viability of how the enriched biochar application can reduce the cost of chemical fertilizer usage.